(untitled) (Tanzania Medical Journal, 2007)
Objective: To determine the knowledge, practice and attitude of Medical students on HIV/AIDS oral manifestations. Materials and Methods: Closed ended self-administered questionnaires were distributed in July 2006 to Fourth (n=150) and fifth (n=114)) year students doing clinical rotations at the Muhimbili National Hospital, Dar es Salaam, Tanzania. Variables included year of study, dichotomous response on knowledge (8 questions) and practices (6 questions); and attitude was evaluated using 5 questions on a 5 point scale. After coding, frequencies for variables were determined using Epi-info software (2000). Results: Students had knowledge that oral lesions were the earliest HIV manifestation commonly observed (65.2%) and were able to identify at least three of the HIV oral manifestations; Candidiasis (93.9%), Hairy Leukoplakia (80.3%) and Kaposi's sarcoma (69.7%). The practice of routine oral examination of every patient was performed by less than half the students (45.5%) and they hardly referred those seen with oral lesions to a dental clinic (18.2%). The attitude of most students was that added precautions should be taken once a patient is known to have HIV/AIDS (95.8%). Knowing the patients HIV/AIDS status prior to being attended was regarded as important (53%) and a few students were of the attitude of not attending a known HIV/AIDS patient. Conclusion: Medical students have adequate knowledge on oral manifestation of HIV/AIDS but could not describe adequately their clinical presentation. Routine practice of oral examination may enhance dental referral. The positive attitude of students observed towards HIV/AIDS patients is encouraging. Tanzania Medical Journal Vol. 22 (1) 2007: pp. 36-39